j = 1 ∏ 2 m sin ( 2 m + 1 π j ) = 2 A + B m − C m , j = 1 ∏ 2 m sin ( 2 m + 2 2 π j − π ) = 2 D + E m − F m
Find A + B + C + D + E + F .
Bonus: Use this result to solve the Wallis product.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
The answer for the first product is 2 1 + 2 m − 2 m We will show this by induction on m. The base case of m=0 is straightforward. Using the double angle identity for sin(x) sin ( 2 m + 1 π j ) = 2 sin ( 2 m + 2 π j ) cos ( 2 m + 2 π j ) = 2 sin ( 2 m + 2 π j ) sin ( 2 m + 2 ( 2 m + 1 − j ) π ) Notice that j = 1 ∏ 2 m sin ( 2 m + 1 π j ) = 2 2 m − 2 1 j = 1 ∏ 2 m + 1 sin ( 2 m + 2 π j ) (The extra 2 2 − 1 appears because sin 4 π got included twice in the previous calculation. Also sin 2 π did not get included but that doesn't matter because it is equal to 1) This completes the proof because 2 1 + 2 m − 2 m ÷ 2 2 m − 2 1 = 2 1 + 2 m + 1 − 2 m + 1
The answer for the second product is 2 2 1 − 2 m We will show this by induction on m. The base case of m=0 is straightforward. Using the double angle identity for sin(x) sin ( 2 m + 2 2 π j − π ) = 2 sin ( 2 m + 3 2 π j − π ) cos ( 2 m + 3 2 π j − π ) = 2 sin ( 2 m + 3 2 π j − π ) sin ( 2 m + 3 2 m + 2 π − ( 2 π j − π ) ) Notice that j = 1 ∏ 2 m sin ( 2 m + 2 2 π j − π ) = 2 2 m j = 1 ∏ 2 m + 1 sin ( 2 m + 3 2 π j − π ) This completes the proof because 2 2 1 − 2 m ÷ 2 2 m = 2 2 1 − 2 m + 1
Bonus: Consider the product j = 1 ∏ 2 m sin ( 2 m + 2 2 π j − π ) sin ( 2 m + 2 2 π ( j + 1 ) − π ) sin 2 ( 2 m + 1 π j ) By the formulae that we just found, this is equal to ( 2 2 1 − 2 m ) 2 sin ( 2 m + 2 2 m + 1 π + π ) ÷ sin ( 2 m + 2 π ) ( 2 1 + 2 m − 2 m ) 2 This simplifies to 2 m + 1 tan 2 m + 2 π Taking the limit as m goes to infinity of each side of the equation gives us 2 π = 1 2 3 2 3 4 5 4 5 6 7 6 . . .
Note: To take the limit of the product at the end we technically need to show that the limit of the product is equal to the product of the limits. To make this a little easier, let n = 2 m . We can simplify each term to 4 j 2 − 1 + f 4 j 2 + e where e and f are small error terms whose most significant term is proportional to n − 2 . The number of terms in which this error gets multiplied is n, so we need to take 4 j 2 − 1 + f 4 j 2 + e to the nth power. We can see that the error terms do go to zero even if they get multiplied n times, so the limit of the product is indeed equal to the product of the limits.
For more information see https://www.3blue1brown.com/sridhars-corner/2018/4/17/wallis-product-supplement-dominated-convergence